Changes of Substance P in the Crevicular Fluid in relation to Orthodontic Movement Preliminary Investigation. (12th March 2013) - Levrini, Luca; Sacerdote, Paola; Moretti, Sarah; Panzi, Silvia; Caprioglio, Alberto
Abstract : Substance P (SP) is a tachykinin released from both the central and the peripheral endings of primary afferent neurons and functions as a neurotransmitter. As a transmitter signaling pain, substance P is involved in nociception and is an extremely potent vasodilator. We found several studies about this neuropeptide especially in relation to parodontology and a few orthodontic reviews. This is because in the past the importance of this neuropeptide in dental element undergoing periodontal inflammation was observed. The aims of the present pilot study was to investigate whether the substance P was present in gingival crevicular fluid in dental elements undergoing orthodontic treatment with Invisalign technique compared to teeth belonging to the same series but not undergoing orthodontic movement. We analysed gengival crevicular fluid (GCF) collected from four young subjects, using a paper cone for a time of 60 seconds. The results showed that SP is present in the gengival sulcus in elements undergoing orthodontic forces during treatment with Invisalign technique and not in the control teeth. During the literature analysis, we have found a lot of papers describing involvement of SP in periodontitis and inflammatory diseases, but further studies are needed in order to demonstrate the role of this neuropeptide during teeth movement.